2010
DOI: 10.1111/j.1755-0998.2010.02951.x
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive, direct real‐time PCR method for sex determination in multiple avian species

Abstract: Polymerase chain reaction (PCR)-based methods to determine the sex of birds are well established and have seen few modifications since they were first introduced in the 1990s. Although these methods allowed for sex determination in species that were previously difficult to analyse, they were not conducive to high-throughput analysis because of the laboriousness of DNA extraction and gel electrophoresis. We developed a high-throughput real-time PCR-based method for analysis of sex in birds, which uses noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Birds from the captive colony were maintained on daily rations of dead laboratory mice (Mus musculus), dead chicken (Gallus gallus) hatchlings, or Classic Bird of Prey diet (Nebraska Brand, North Platte, NE) supplemented with Vionate Ò (Gimborn US, Atlanta, GA). Because screechowls are not sexually dimorphic, sex was determined by gene amplification (CHD1-Z and CHD1-W) using realtime PCR analysis (Brubaker et al 2011), and results were all confirmed at necropsy.…”
Section: Animalsmentioning
confidence: 99%
“…Birds from the captive colony were maintained on daily rations of dead laboratory mice (Mus musculus), dead chicken (Gallus gallus) hatchlings, or Classic Bird of Prey diet (Nebraska Brand, North Platte, NE) supplemented with Vionate Ò (Gimborn US, Atlanta, GA). Because screechowls are not sexually dimorphic, sex was determined by gene amplification (CHD1-Z and CHD1-W) using realtime PCR analysis (Brubaker et al 2011), and results were all confirmed at necropsy.…”
Section: Animalsmentioning
confidence: 99%
“…However, considerable variation may occur in the quantity and the quality of the recovered DNA, depending on whether the samples are fresh plucked feathers (Harvey et al 2006) or shed feathers (Hogan et al 2008). Buccal cells collected using cotton swabs provide another source of DNA that is now regularly used in a number of species: amphibians (Pidancier et al 2003;Broquet et al 2007a), fish (Smalley & Campanella 2005), mammals (Mitrecic et al 2008) and more rarely birds (Bush et al 2005;Handel et al 2006;Brubaker et al 2011). Nondestructive and noninvasive samples such as feathers and buccal swabs may contain small quantities of DNA and ⁄ or degraded DNA.…”
Section: Introductionmentioning
confidence: 99%
“…They were then immersed in a 30% sucrose solution for approximately 30 h to ensure cryoprotection (until the brains sank to the bottom of the vial) and then frozen at -80 8C. The sex of the hatchlings was determined genetically following the method of Brubaker et al (2011). The sex of the hatchlings was determined genetically following the method of Brubaker et al (2011).…”
Section: Egg Injections Experimental Groups and Tissue Collectionmentioning
confidence: 99%
“…The brains were shipped frozen on dry ice from USGS Patuxent Wildlife Research Center to McGill University, where they were stored at -80 8C until they were processed for neuroanatomical measurements as described below (Histological processing of brains) following Guigueno et al (2018Guigueno et al ( , 2016. The sex of the hatchlings was determined genetically following the method of Brubaker et al (2011).…”
Section: Egg Injections Experimental Groups and Tissue Collectionmentioning
confidence: 99%